International experience in the context of pharmaceutical care introduction in Poland - Oberska , Joanna; Prusaczyk , Artur; Żuk, Paweł; Jurewicz, Błażej; Guzek, Marika; Bogdan, Magdalena (Journal of Education, Health and Sport, 2022)
The Pharmacist Profession Act and planned pharmaceutical services introduce many changes in community pharmacies, which require effective and efficient implementation. The below article aimed to analyse international experiences in the field of pharmaceutical care and to identify solutions that could be implemented in Poland. United States, United Kingdom, the Netherlands, Sweden, Austria and Australia were considered. These countries were analysed in terms of which pharmaceutical care services are provided, how pharmaceutical care was firstly introduced, what compensation pharmacists receive for additional services and what IT systems are used.